"A arte de viver": (re)apresentando a experiência de adolescentes vivendo com HIV/Aids - Berni, Vanessa Limana (2013)
The aim of this Master Dissertation is to (re)presented the experience of perinatally infected HIV adolescents, treated in a public hospital located in Brazil‟s sul. Specifically, we aimed: to socialize experiences of research in a specialized health service; to discuss the conceptions about adolescence/adolescent and how are described by the interviewees; and to understand how representations of AIDS impact their social/emotional relationships and the construction of their identity. We conducted semi structured one-on-one interviews with 6 adolescents (ages between 11-14 years old). The interpretation of information is based in the Critical Social Psychology, Theory of social representations and other interdisciplinary theoretical productions about identity, adolescence and HIV/AIDS. Results were presented in three manuscripts: (a) Research Movements in a specialized HIV/AIDS service: interdisciplinarity, reception and access to the adolescents : to socialize experiences of research in a specialized health service for HIV/AIDS children and adolescents. (b) Adolescence (Re)presented from the view of critical social psychology : to (re)introduce some elements to construct an alternative conception of adolescence/adolescent that goes along with the ontological and epistemological presuppositions of the Critical Social Psychology. (c) Adolescents living with HIV/AIDS: identity and social representations in dialogue : to present and analyze the experience of perinatally infected HIV adolescents, to understand how representations of AIDS impact their social/emotional relationships and the construction of their identity; In conclusion, it was emphasized that recognizing the adolescents as participant on decisions regarding their body/treatment might bring benefits as: the strengthening of health care services attachment and increasing of medication adherence. It was suggested the implementation of dialogical spaces, where adolescents (and also family members) can not only share their experiences with another adolescents and health professionals but as an interdisciplinary daily-space to clarify doubts/questions about adolescence and HIV/AIDS. Finally, it was highlighted the need for strategies that deconstruct traditional and negative representations of AIDS in society, so that those adolescents, and other people living with HIV/AIDS, may ease their fears of suffering prejudice. Keywords: Critical Social Psychology, Adolescence, Adolescents, HIV/AIDS, Social Representations.